(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To evaluate the ultrastructure of the choriocapillaris, retina and optic nerve (ON) in citicoline-treated versus non-treated rabbits at the late time point after inducing non-infectious anterior and intermediate uveitis. Methods: The ultrastructure of the rabbit choriocapillaris, retina and ON was evaluated at day 55 after the initiation of uveitis. Results: Experimentally induced uveitis caused neurodegenerative changes in the retina and ON. Neuroprotective treatment activated intracellular compensative processes resulted in reduced signs of hydropic degeneration and normalized cell ultrastructure, and contributed to the activation of metabolism in ON glial cells and axoplasm. Conclusion: Neuroprotective treatment for non-infectious anterior and intermediate uveitis resulted in a reduction in neurodegenerative changes in the retina and ON.